Timing of Chemotherapy and Radiotherapy Following Breast-Conserving Surgery for Early-Stage Breast Cancer: A Retrospective Analysis - Chen, Si-Ye; Tang, Yu; Wang, Shu-Lian; Song, Yong-Wen; Fang, Hui; Wang, Jian-Yang; Jing, Hao; Zhang, Jiang-Hu; Sun, Guang-Yi; Zhao, Xu-Ran; Jin, Jing; Liu, Yue-Ping; et al. (Frontiers in Oncology, 2020)
Purpose To investigate the effect of chemotherapy and radiotherapy timing after breast conserving surgery (BCS) on recurrence and survival of women with early-stage breast cancer. Patients and Methods We retrospectively analyzed 900 patients who underwent BCS followed by both adjuvant chemotherapy and radiotherapy. Of these, 488 women received chemotherapy first (CT-first group) while the other 412 received radiotherapy first (RT-first group). Locoregional recurrence (LRR), distant metastasis (DM), disease-free survival (DFS), and overall survival (OS) rates were calculated using the Kaplan-Meier method and further confirmed with propensity-score matching (PSM) and the Cox proportional hazards model. The optimal cut-off value of interval time from surgery to the start of chemotherapy was calculated by Maxstat. Results The median follow-up was 7.1 years. In pre-match analysis, the CT-first group had a significantly higher 8-year DFS than the RT-first group (90.4% vs. 83.1%, P = 0.005). PSM analysis of 528 patients indicated that the 8-year DFS (91.0% vs. 83.3%, P = 0.005) and DM (8.6% vs. 14.6%, P = 0.017) were significantly better in the CT-first group, but that the OS (P = 0.096) and LRR (P = 0.434) were similar. We found the optimal cut-off value of interval from surgery to chemotherapy was 12 weeks. Patients starting chemotherapy later than 12 weeks after surgery had significantly inferior survival outcomes. Conclusion For women with breast cancer who require both chemotherapy and radiotherapy after BCS, adjuvant chemotherapy should be started within 12 weeks. Delaying the initiation of radiotherapy, for administration of long-course chemotherapy, does not compromise outcomes.